Husyckie wątki religijne w najnowszym czeskim komiksie historycznym - Guzek, Mariusz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The creators of Czech historical comics are active participants in the debate on national identity and the role of historical memory in today’s political practices. Above all, they preferred to refer to the events of the past century, which defined such currently important concepts as responsibility, heroism and sacrifice, among other things. However, the history of Jan Hus and the Hussite movement, recalled on this anniversary, proved just as relevant to comics’ strategies. The article discusses inspirations and references in projects such as the two-volume albums by Z. Ležak and M. Kocián, the evangelistic notebooks by A. Mrazek and the online frames by a cartoonist who signs his works with the pseudonym jaz.